Is Dietary Iodine Intake Excessive According to the Theoretical Model of Healthy Dietary Intake Pattern in Pregnant Women and Schoolchildren: Water, Salt, or Food? - Candido, Aline Carare; Ribeiro, Sarah Aparecida Vieira; Macedo, Mariana de Souza; Fontes, Edimar Aparecida Filomeno; Souza, Eliana Carla Gomes De; Lopes Duarte, Maria Sonia; Priore, Silvia Eloiza; Peluzio, Maria do Carmo Gouveia; Milagres, Regina Célia Rodrigues de Miranda; Franceschini, Sylvia do Carmo Castro (Frontiers in Nutrition, 2021)
Introduction: Iodine deficiency during pregnancy can cause hypothyroidism and goiter; in schoolchildren, it can cause reduced intelligence quotient. In excess, iodine can cause thyroiditis, goiter, and Hashimoto's hypothyroidism. Currently, schoolchildren and pregnant women are classified as risk groups for excessive iodine intake and iodine deficiency, respectively. Thus, determining iodine from all sources of consumption is important for intervention planning. Objective: To construct a theoretical model for the iodine intake of schoolchildren and pregnant women of a city in the Zona da Mata Mineira region, considering a healthy diet, salt consumption and water intake. Methodology: The dietary iodine intake of pregnant women was analyzed based on a dietary iodine table compiled from an international database. A dietary plan was prepared following the Brazilian Food Guide. Iodine concentration of different salt brands sold in local establishments was checked, and drinking water samples from healthcare facilities were analyzed. A descriptive and exploratory statistical analysis was performed and the results were presented in absolute and relative frequencies, and measures of central tendency and dispersion. Results: According to the proposed diet, pregnant women and schoolchildren would have a daily intake of 71.6 μg and 71 μg, respectively. Thirteen salt brands were evaluated, 69.2% complied with the legislation and the mean iodine content was 29.88 mg. The mean concentration of iodine in water was 25 μg iodine/liter and 14 μg iodine/liter, respectively, in summer and autumn. Considering the intake of food, salt, and drinking water according to the proposed dietary plan, the daily intake for pregnant women would be 279.5 and 253.5 μg for schoolchildren. Conclusion: The daily iodine intake of schoolchildren and pregnant women according to this theoretical model was excessive, considering a healthy dietary pattern. This theoretical model can guide actions and public policies aimed at targeting all forms of iodine intake.